Advanced biomaterials for radiation-induced dermatitis: from pathophysiological mechanisms to translational interfaces - Ma, Cheng; Zhu, Haijun; Liu, Chunlei; Wang, Wenxin (Frontiers in Materials, 2025)
Radiation-induced dermatitis (RID) remains one of the most prevalent and therapeutically challenging complications in cancer radiotherapy, significantly impairing patient quality of life and treatment adherence. In recent years, bioengineered materials have emerged as promising platforms for the prevention and treatment of RID through multifunctional mechanisms. This review systematically summarizes the current landscape of biomaterials applied to radiation-induced skin injury, focusing on the regulation of oxidative stress, inflammatory responses, and regenerative tissue repair. Beyond conventional classifications based on function—such as barrier protection, therapeutic delivery, and tissue reconstruction—we highlight advances in biomaterial design mechanisms. Particular attention is given to surface properties, including roughness, electrical charge, and crosslinking dynamics, which influence immune modulation and cellular behavior at the wound interface. Mechanistic insights are discussed regarding reactive oxygen species-responsive materials, macrophage phenotype regulation, and vascular regeneration in irradiated tissue environments. Comparative analyses with conventional wound dressings, such as alginate-based and silver-containing materials, underscore the superior therapeutic efficacy of biointeractive and stimuli-responsive systems. In addition, emerging technologies including three-dimensional bioprinting, exosome-inspired scaffolds, and multi-responsive drug carriers are critically evaluated for their translational potential. Clinical trials, regulatory pathways, and manufacturing considerations are also discussed to outline future directions for clinical implementation. This review provides a comprehensive and mechanism-driven perspective on next-generation biomaterials for precision treatment of radiation-induced skin damage.